La crónica, el género literario del periodismo que merece sobrevivir - Jordán Correa, Dennys (2016)
The writing of journalistic genres requires techniques and skills propitious and independent of the theoretical knowledge of the profession. It is the search for indispensable tools to achieve a playful narrative that addresses urban themes enriched with anecdotes, experiences and the experiential reflection of situations. Unlike other genres, the chronicle is complicated because it makes a deep immersion in each story in order for the reader to identify with it; For that reason, it uses literary resources that shake the history and show that any conjuncture can become main axis. In the chronicle, the journalists put themselves in the shoes of the characters, smelling, perceiving, observing; The latter aspect involves the use of multiple resources without departing from reality. However, despite being an enriching genre, not all journalists can successfully narrate because there are no schools designed for this purpose; And, in the media itself, the sustainability of these stories is ephemeral, first because it takes time, research, intimidation with the characters; Secondly, there is no room for the number of characters that are produced and, finally, readers have not created the need for their reading; Hence the need to manage the necessary tools to teach the writing of this genre and the delight of it. But the chronicle is intended to save the ink and paper from oblivion. This is acknowledged by Álex Grijelmo, the author of the book "The style of the journalist" in an interview given to El País newspaper last May where he says that if print journalism should resort to chronicles and that the presence of this journal should be accentuated Gender in the face of the inability of the printed media to compete with news with radio, television or the internet.